Retraction Note to "Evaluating the Effect of Studying Computer Ethics and Computer Ethics Rules and Regulations on Computer Ethics at Work" [Cloud Computing and Data Science, Volume 1 Issue 1 (2020), 23-33] - Universal Wiser Publisher (Cloud Computing and Data Science, 2025)
The Editor-in-Chief and the Editorial Office of Cloud Computing and Data Science (CCDS) have retracted the following article: Alsultanny Y. Evaluating the Effect of Studying Computer Ethics and Computer Ethics Rules and Regulations on Computer Ethics at Work. Cloud Computing and Data Science. 2020; 1(1): 23-33. This article has been retracted at the request of the Editor-in-Chief. Following a journal-wide investigation, it was identified that this article falls outside the scope of the journal, and does not align with the thematic focus or subject matter requirements as outlined by the journal's editorial policies. The retraction is in accordance with the Committee on Publication Ethics (COPE) guidelines, ensuring the integrity of the publication record is maintained. As part of journal's ongoing efforts to improve the quality of publications, the editorial office will continue to rigorously conduct preliminary review and peer review to ensure that only manuscripts that align with the journal's scope and meet the highest academic standards are published. The editorial office sincerely apologize for any confusion or inconvenience this retraction may have caused. The author has not responded to the Editor about this retraction notice.